2000
DOI: 10.1007/s002130000481
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptors and reward in the rat: a conditioned place preference study

Abstract: The aversive effects of cannabinoid agonists and the rewarding effect of the cannabinoid antagonist are suggestive of a cannabinergic tone in the rat brain. Further research is needed to determine the precise relationship of that tone with the reward pathways of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
4

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 33 publications
7
100
1
4
Order By: Relevance
“…This work confirms previous findings that cannabinoid agonists are aversive to rats, as shown by the formation of a conditioned place aversion (McGregor et al, 1996;SanudoPena et al, 1997;Mallet and Beninger, 1998;Cheer et al, 2000). D 9 -THC-treated adult rats avoided the drug-paired side after both four and eight contextual pairings, while adolescent rats only showed a trend toward place aversion, and only after eight pairings.…”
Section: Acute Aversive Effects Of Thcsupporting
confidence: 91%
See 1 more Smart Citation
“…This work confirms previous findings that cannabinoid agonists are aversive to rats, as shown by the formation of a conditioned place aversion (McGregor et al, 1996;SanudoPena et al, 1997;Mallet and Beninger, 1998;Cheer et al, 2000). D 9 -THC-treated adult rats avoided the drug-paired side after both four and eight contextual pairings, while adolescent rats only showed a trend toward place aversion, and only after eight pairings.…”
Section: Acute Aversive Effects Of Thcsupporting
confidence: 91%
“…This hypothesis has not to our knowledge been tested using animal models. Rats generally find cannabinoids aversive, with D-9-tetrahydrocannabinol (D 9 -THC) and synthetic cannabinoids producing conditioned place aversion (Parker and Gillies, 1995;McGregor et al, 1996;Sanudo-Pena et al, 1997;Mallet and Beninger, 1998;Cheer et al, 2000) and conditioned taste avoidance (Parker and Gillies, 1995;McGregor et al, 1996). Reports of dysphoria and panic by human cannabis users (Hall et al, 1994) suggest these aversive effects may sometimes have a human correlate.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas most recreational users of cannabis experience a state of euphoria, others also report dysphoria and anxiety particularly at the beginning of cannabis consumption (Greg et al, 1976;Thomas, 1993;Grinspoon and Bakalar, 1997;Williamson and Evans, 2000). Human reports are in agreement with animal studies showing that D 9 -tetrahydrocannabinol (THC) and other synthetic cannabinoid agonists can induce both rewarding and aversive effects, as revealed in the place conditioned paradigm (Sañudo-Peña et al, 1997;Cheer et al, 2000;Valjent and Maldonado, 2000). The endogenous opioid system seems to play an important role in the different effects produced on the reward circuit after cannabinoid administration.…”
Section: Introductionmentioning
confidence: 77%
“…Previous reports have found that lower doses of THC are not effective as conditioning stimuli in place conditioning procedures (Mallet and Beninger, 1998;Parker and Gillies, 1995;Robinson et al, 2003). In contrast, higher doses of cannabinoids such as CP 55,940 (McGregor et al, 1996), WIN 55212-2 (Chaperon et al, 1998), THC (Sanudo-Pena et al, 1997); (Cheer et al, 2000); (Hutcheson et al, 1998); (Parker and Gillies, 1995), and HU210 (Cheer et al, 2000) produced aversion in place conditioning procedures in both rats and mice. Further, the aversive effects produced by THC were blocked by the cannabinoid receptor antagonist, SR141716A (Chaperon et al, 1998), suggesting that these effects were CB1 receptor-mediated.…”
Section: Place Conditioning Effects Of Thc and Cbdmentioning
confidence: 92%